PENGEMBANGAN INSTRUMEN EVALUASI BELAJAR COMPUTER BASED INTRUCTION (CBI) DENGAN MODEL DRILL INTERAKTIF SEBAGAI PROSES EVALUASI BELAJAR PADA MATA PELAJARAN SISTEM KOMPUTER - Nuriati July; Muhammad Amin (Universitas Negeri Medan, 2022)
AbstractThis research aims to find out how the development of computer based instruction (cbi) evaluation instruments with interactive drill models of computer system subjects in vocational schools and the feasibility of using computer based instruction (cbi) learning evaluation instruments with interactive drill models of computer system subjects in smk. This research was conducted on students of class X Majoring in Computer Engineering and Private Vocational Network Citra Abdi Negoro. Media development procedures are carried out by Research and Development methods or better known as R&D and use analysis design models, design, development, implementation and evaluation (ADDIE) but in the development of this research is limited at the implementation stage. Based on the data obtained during the study, validation results from the content expert get a final interpretation of (5,72) with very feasible criteria. Validation results from media experts get a final interpretation of (3,83) with decent criteria. In small group trials it was 82.20% and in large group trials it was 89.04%. From the practicality assessment obtained from the student's response to small and large group trials have the category